Euklidischer Zusammenhang der Art von Cartan des metrischen Linienelementraumes - Bliznikas, V. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Близникас. Евклидова связность картановского типа в метрическом пространстве линейных элементовV. Bliznikas. Kartano tipo euklidinis sąryšis metrinėje tiesinių elementų erdvėje